Reinforcement Effect of Polypropylene Sheet on Soil Strength with Cement - Umair Sajjad; Khurram Taj; Khuda Bukhsh; Umar Saeed; Kashif Alam (Journal of ICT, Design, Engineering and Technological Science, 2022)
Following thorough soil investigation, the designs for the foundations and other structures are made. The foundations and structures are more reliable and safer when the right soil is used. In this study, cement-coated Polypropylene (PP) sheets were employed to strengthen the soil, enhancing its shear strength and other characteristics. Two (2) soil samples were taken to compare the average outcomes and minimize error. Before using PP sheets for soil reinforcement, various index and strength parameters, such as breaking tensile strength, elastic modulus, and breaking and fusion points, among others, were examined. Properties like liquid and plastic limit, specific gravity, Maximum Dry Density (MDD), and Optimum Moisture Content (OMC) were examined as discussed. Reinforcement of 0%, 0.05%, 0.15%, and 0.25% were applied and tested against shear strength evaluation with the help of a direct shear test. An increase in strength is observed in soil samples 1 and 2, i.e., 1.27, 2.25, 2.27 and 1.28, 1.42, 1.65, and 1.79 in kg/cm2, respectively. Similarly, unconfined compression strength was observed to increase from 0.0692 MPA to 0.0942 MPA, which is 11.68% and 35.94% increment in soil samples 1 and 2 at 0% and 0.05% reinforcement, respectively.